Analysis Of The Selection Of Freight Forwarder Services By Using Anaythical Hierarchy Process (AHP) Method To Minimize The Cost Of Shipping Exported Goods - M Tirtana Siregar; Dwi Putri Andiani (AIBPM Publisher, 2019)
This study aimed to minimize the cost of shipping export products. The selection of freight forwarders in shipping export goods is performed by direct appointment, this can affect the level of customer satisfaction and the cost of shipping exported goods issued to be high. The method used to select freight forwarders is the Analytical Hierarchy Process (AHP) Method. Calculation of the selection of freight forwarder services by using the Analytical Hierarchy Process (AHP) method can determine the type of freight forwarder services that have the highest weight and the calculation of shipping costs of export goods, furthermore can find out the comparison of costs incurred by the company between using several types of freight forwarder services by using one type of freight forwarders who have the highest weight in the calculation of the Analytical Hierarchy Process (AHP) Method. There are four steps to select freight forwarder services by using the Analytical Hierarchy Process (AHP). Pairwise comparisons is a matrix can be used that can compare weights between criteria and between alternatives. The company in selecting freight forwarder services should use the Analytical Hierarchy Process (AHP) Method due to Analytical Hierarchy Process (AHP) method is implemented to generate an initial feasible solution of freight forwarders performance problems.